Peran Emotional Shopping Dalam Membentuk Impulse Buying Pada Konsumen Hyermart Di Surakarta - Marjam Desma Rahadhini (Jurnal Sains Sosio Humaniora, 2021)
This study aims to analyze the role of emotional shopping informing impulse buying. This research is a survey at Hypermart in Surakarta. The population of this research is consumers who have made a purchase at Hypermart Surakarta. The sampling method used non-probability with a purposive sampling with 110 respondents. Data analysis using Structural Equation Modeling (SEM). The validity test used Confirmatory Factor Analysis (CFA) and the reliability test used Cronbach's Alpha. The results show that price discount and store atmosphere affect emotional shopping, price discount and store atmosphere affect impulse buying, emotional shopping affects impulse buying, emotional shopping does not mediate the effect of a price discount on impulse buying, and emotional shopping does not mediate the effect of store atmosphere against impulse buying